Legal Review of the Use of Song Without Consent in Accordance with Law No. 28 of 2014 - Taharah, Amanah; Prasetyo, Muhammad Arif; Pamellia, Amanda Okta; Fauza, Akbar Reza (IJBLE Scientific Publications Community Inc., 2025)
To produce aesthetically pleasing compositions, musicians employ a variety of instrumental sounds. Copyright refers to the exclusive right of a creator to maintain ownership of their work and to derive economic benefit from it. Under copyright law, the unauthorized use of musical works is strictly prohibited. This study aims to: (1) examine the enforcement of Law No. 28 of 2014 by the Indonesian government in protecting the rights of songwriters; and (2) analyze the implementation of licensing agreements by both producers and users. Employing a normative legal approach, this study emphasizes that the government plays a crucial role in protecting music creators and copyright holders from infringement through legal enforcement. Licensing and registration constitute fundamental components of copyright protection. Moreover, the government is expected to take active measures in raising public awareness about the importance of respecting and protecting intellectual property rights. The primary purpose of licensing agreements is to prevent legal disputes and to deter unauthorized actions by third parties that violate the stipulated terms and conditions.